OBTENTION OF DISTILLATE WATER TO LABORATORY USING SOLAR ENERGY - Percy Gutiérrez Salas (2019)
A solar distillator was designed, built and operated in order to obtain distilled water with conductivity not higher than 6 uS/cm to be used in analytical laboratories. This equipment is composed by a cylindrical parabolic solar concentrator with a focal axis made of a black copper pipe inside of which flowed water.The pipe was half filled to allow the vapor flow towards the condensed plate located under the shadow generated by the parabolic collector. The average efficiency was 0,3 L distilled water/ m2.day.